DNA Extraction and PCR Optimization of Coffea arabica L. and Coffea canephora Pierre ex A. Froehner - Risa Riani Ramlan; Essy Harnelly; Lenni Fitri (Postgraduate, University of Mataram, 2024)
DNA isolation is an important step for further molecular analysis. Coffee plants contain polysaccharides, polyphenols, and secondary metabolites which can contaminate the results of DNA isolation. This study was conducted to isolate DNA from arabica and robusta coffee leaves using a modified CTAB method and PCR optimization for amplification of matK and rbcL genes. DNA was isolated using buffers (CTAB 10%, PVP 1%, β-mercaptoethanol 1%, Tris-HCl 1M, NaCl 5M, and EDTA 0.5%), and eluted with TE-RNase. Genomic DNA of ten coffee plants was successfully isolated with concentrations ranging from 33-146 nm/µL with purity (A260/A280) 1.7-1.9. Based on the genomic DNA isolated, matK and rbcL genes were amplified with initial denaturation conditions of 94°C (for 1 minute of matK and 4 minutes of rbcL) followed by 35 cycles of denaturation at 94°C for 30 seconds, annealing (adjusted to each primer), and extension at 72°C for 1 minute. The optimal PCR conditions were effective to amplify matK (900 bp) and rbcL (600 bp) genes. Thus, the modified DNA isolation method and PCR optimization can be used as an efficient tool for further molecular analysis of Coffea arabica L. and Coffea canephora Pierre ex A. Froehner.